Motivation, interest, learning a Hubungan Motivasi Belajar dan Minat Belajar terhadap Prestasi Belajar Mahasiswa Mata Kuliah Pengantar Manajemen - Syardian sah (Jurnal Manajemen dan Keuangan, 2016)
This study was conducted to determine the relationship of learning motivation and interest in learning on student achievement of economic faculty majoring in management, especially in the introductory courses of management. The number of students in an introductory course management department management level 1 EKM A two semesters as many as 40 students were used as source material for data retrieval. This study only measures the variables of learning motivation (X1), interest in learning (X2) and achievement (Y). For the data on the variables of learning motivation and interest in learning by distributing questionnaires given to 40 students. While the data for student achievement is taken from the value of an introductory course on the management students. To determine the relationship between these variables do some analysis that test reliability analysis and correlation tests. Based on the test results of 36 questionnaires statement can be expressed realiabilitas well as Cronbach alpha value was 0.82 and have a positive relationship because the value of the correlation coefficient of 0.16 is positive and close to zero. While the coefficient of determination of 0.028 means that the motivation and interest of 2.8% effect on learning achievement.